Effect of Intraoperative Hypothermia on Post-anesthesia Recovery in Elderly Patients Undergoing Abdominal Surgery (Asian Journal of Pharmaceutics (AJP), 2025)
Introduction: Intraoperative hypothermia (IOH) is a common concern in elderly patients undergoing abdominalsurgery, potentially leading to prolonged recovery, increased post-operative complications, and extended hospitalstays. Understanding the effects of hypothermia on recovery and patient comfort is crucial for improving surgicaloutcomes and optimizing healthcare resource utilization. Methods: The research investigates secondary datafrom peer-reviewed journals published between 2015 and 2024 to examine how IOH affects elderly patientsduring abdominal surgery. Medical research from PubMed and Scopus electronic databases led to data collectionfor studies that contained relevant clinical, along with physiological and psychological data. Results: Theresearch shows that hypothermia during surgery directly affects treatment duration and complications, along withpatient comfort and recovery time, as well as hospitalization lengths. Research has shown hypothermia disturbstemperature regulation and postpones anesthetic emergence and raises infection risk, and interferes with earlyrehabilitation decisions, which extend hospital duration. Discussion: In older abdominal surgery patients, IOHwas repeatedly connected to delayed recovery, higher post-operative problems, discomfort, worse mobility, andlonger hospital stays. The results underline the vital requirement of proactive perioperative warming techniquesto guarantee patient safety and comfort as well as to enhance results. Conclusion: All surgical patients shouldmaintain normal body temperature, but elderly patients especially need normothermic care to improve surgicalrecovery results. Controlling temperature through active methods, along with regular monitoring, helps minimizesurgical complications and reduces hospital stay time because of its vital role in perioperative care.